cDNA selection: efficient PCR approach for the selection of cDNAs encoded in large chromosomal DNA fragments. - Parimoo, S (1991)
Identification of coding segments in large fragments of genomic DNA is a recurrent problem in genome mapping and positional cloning studies. We have developed a rapid and efficient protocol to achieve this goal, based on hybridization of cDNA fragments to immobilized DNA and recovery of the selected cDNAs by the PCR. The procedure permits rapid cloning of cDNA fragments encoded by large genomic DNA fragments, groups of yeast artificial chromosomes, or cosmids and has the potential to directly enrich cDNAs encoded in chromosome segments. By this approach we have been able to identify several non-major histocompatibility complex class I clones from a yeast artificial chromosome that includes the HLA-A locus.